2017
DOI: 10.1038/srep45462
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression of cuticular protein genes based on Locusta migratoria transcriptome

Abstract: Many types of cuticular proteins are found in a single insect species, and their number and features are very diversified among insects. The cuticle matrix consists of many different proteins that confer the physical properties of the exoskeleton. However, the number and properties of cuticle proteins in Locusta migratoria remain unclear. In the present study, Illumina sequencing and de novo assembly were combined to characterize the transcriptome of L. migratoria. Eighty-one cuticular protein genes were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 50 publications
0
38
0
Order By: Relevance
“…However, the functions of HR39 and its regulatory target genes during insect moulting are rarely reported. In the present study, we identified a nuclear receptor factor LmHR39 from the transcriptome and genome database of a locust species (Wang et al ., ; Zhao et al ., ). Similarly to HR39 proteins from other species, and to betaFTZ‐F1 (Ohno and Petkovich, ; Yussa et al ., ; Cruz et al ., ; Liu et al ., ), LmHR39 contains a LBD and a DBD (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the functions of HR39 and its regulatory target genes during insect moulting are rarely reported. In the present study, we identified a nuclear receptor factor LmHR39 from the transcriptome and genome database of a locust species (Wang et al ., ; Zhao et al ., ). Similarly to HR39 proteins from other species, and to betaFTZ‐F1 (Ohno and Petkovich, ; Yussa et al ., ; Cruz et al ., ; Liu et al ., ), LmHR39 contains a LBD and a DBD (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The cDNA sequence of LmHR39 was obtained from an L. migratoria transcriptomic database (Zhao et al ., ) and verified against the genome of L. migratoria (Wang et al ., ). The ExPASy tool (https://web.expasy.org/translate/) was used to conceptually translate the LmHR39 cDNA sequence into its putative protein product.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we identified a few individual proteins that could not be assigned to the major protein function categories. The altered abundance of the cuticular protein precursor (NP_001167611.1) and chitinase-like protein (XP_016773072.1), compounds of insect cuticle layers (Zhao et al 2017), suggests a disruption in the honey bee exoskeleton after Varroa infestation. The down-regulation of the circadian clock-controlled protein (XP_001122696.1) suggests circadian behavioural rhythm disorder (Fuchikawa et al 2017).…”
Section: Proteins Of Other Categoriesmentioning
confidence: 99%
“…Analysis of insect genomes showed that around 1% of protein-coding genes are represented by CP (Ioannidou et al, 2014). CPs have been identified and analyzed on genomic, transcriptomic, or proteomic levels in more than 20 insect species (Shofuda et al, 1999;Adams et al, 2000;Consortium, 2006;He et al, 2007;Togawa et al, 2007;Futahashi et al, 2008;Cornman & Willis, 2009;Gallot et al, 2010;Liang et al, 2010;Werren et al, 2010;Carrasco et al, 2011;Suetsugu et al, 2013;Sadd et al, 2015;Micas et al, 2016;Jan et al, 2017;Yang et al, 2017;Zhao et al, 2017;Zhou et al, 2017;Pan et al, 2018). However, research related to CPs has mostly focused on Diptera and Lepidoptera.…”
Section: Introductionmentioning
confidence: 99%